PENGARUH PENYULUHAN KANKER SERVIKS TERHADAP PENGETAHUAN WANITA USIA SUBUR TENTANG PEMERIKSAAN IVA TEST DI KAMPUNG PEGADING DAN WILAYAH KERJA PUSKESMAS KRAMATWATU - Nuria Fitri Adista; Ika Apriyanti; M. Mansur Halwani (Poltekkes 'Aisyiyah Banten, 2021)
Cervical cancer is a public health problem both in the world and in Indonesia. Cervical cancer is one of the most common cancers affecting women worldwide and has a wide psychosocial impact, especially for patients and their families. Until now, cervical cancer is the leading cause of death in developing countries in relation to the high incidence and mortality rate due to cervical cancer (1) The incidence of cervical cancer mortality in developing countries ranks first as a cause of cancer death in women of reproductive age, reaching nearly 80 % of cases (2) Based on data from WHO (World Health Organization) in 2014, cancer is the second leading cause of death from all deaths from non-communicable diseases, namely 7.6 million deaths or around 21%. According to data from the World Health Organization, it is known that there are 493,243 cervical cancer sufferers per year with a maternal mortality rate due to cervical cancer of 273,505 people per year (3). The purpose of this study was to determine the effect of cervical cancer counseling on the knowledge of women of childbearing age about the IVA test in Pegadingan Village, the working area of ​​the Kramatwatu Community Health Center.This research method is pre experimental design with one group pre-test-post-test design, that is, research is conducted by giving a pre-test before the intervention is carried out. After being given the information / intervention, the same post test was carried out as the pre test. The population in this study were women of childbearing age aged 25-50 years in the village of Pegadiangan, the working area of ​​the Kramatwatu Community Health Center in 2019 with a total of 1300 with a sample size of 93 and the sample technique in this study was to use accidental sampling. Data collection in this study uses primary data. Primary sources are data sources that directly provide data to data collectors (22). The instrument that will be used in this research is a questionnaire about interest about the IVA examination.The results of the study The knowledge of women of childbearing age about the Visual Inspection of Acetic Acid (IVA) before being given cervical cancer counseling, the average score was 59.46. The knowledge of women of childbearing age about the visual inspection of acetic acid (IVA) after being given cervical cancer counseling, the average score was 76.11. There is a significant influence between the knowledge before and after being given cervical cancer counseling, this is shown from the results of the Wilcoxon test statistical test that the p-value is 0.000 where the sig 2 tailed value <0.05. For health workers to be more optimal in providing reproductive health promotion, especially regarding early detection of cervical cancer and IVA examination.